1998
DOI: 10.2134/agronj1998.00021962009000050010x
|View full text |Cite
|
Sign up to set email alerts
|

Field Validation of Soil Solute Profiles in Irrigated Cotton

Abstract: Management of water and fertilizer N are important aspects of cotton production in the desert Southwest. GOSSYM, a cotton growth simulation model, has been used extensively to manage these inputs. Our objectives were to further validate GOSSYM by comparing model‐simulated and measured soil NO‐3‐N profiles, to evaluate GOSSYM's potential as a management tool under irrigated growing conditions in the desert part of the U.S. Cotton Belt, and to address questions about the way GOSSYM simulates NO‐3‐N movement thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…As such, they comprise a convenient system for analysis of dynamic cellular responses to pathogens and other environmental stimuli under controlled laboratory conditions (Goldberg et al, 1989; Guinel and McCully, 1986, 1987; Gochnauer et al, 1990). Cotton cultivars with altered border cell number can be used in future studies to determine whether such phenomena function in variable root–soil interface properties and in crop performance in the field (Unruh and Silvertooth, 1996a, b; Norton and Silvertooth, 1998). Of particular interest are observations of differential resistance to fungal pathogens including Verticillium and Fusarium (Bolek et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As such, they comprise a convenient system for analysis of dynamic cellular responses to pathogens and other environmental stimuli under controlled laboratory conditions (Goldberg et al, 1989; Guinel and McCully, 1986, 1987; Gochnauer et al, 1990). Cotton cultivars with altered border cell number can be used in future studies to determine whether such phenomena function in variable root–soil interface properties and in crop performance in the field (Unruh and Silvertooth, 1996a, b; Norton and Silvertooth, 1998). Of particular interest are observations of differential resistance to fungal pathogens including Verticillium and Fusarium (Bolek et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…According to this pattern, N fertilization might not be needed for cotton during the first month. Cotton N use efficiency was enhanced without preplant N application (Norton and Silvertooth, 1998). Ebelhar et al (1996) observed a significant increase in cotton yield when N was applied as two equal splits, one at planting and the other at pinhead square stage in Mississippi.…”
Section: Introductionmentioning
confidence: 99%